2018
DOI: 10.4081/monaldi.2018.890
|View full text |Cite
|
Sign up to set email alerts
|

Linear probe 19-gauge endobronchial ultrasound diagnosis of a benign chondroid hamartoma

Abstract: We report a case of a 68-year-old gentleman, found to have a right hilar soft tissue mass whilst undergoing CT staging for prostate cancer. MRI imaging showed a heterogeneous, enhancing solid mass without evidence of fat content. A linear probe endobronchial ultrasoundguided transbronchial needle aspiration was performed using a 19G needle. This confirmed the diagnosis of a benign chondroid hamartoma, avoiding the need for more invasive surgical biopsy. Case ReportA 68-year-old gentleman with a recent diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Certainty diagnosis of mediastinal hamartoma is based on recognition of the characteristic fibromyxoid stroma or chondroid material with variable amounts of ciliated and nonciliated epithelium, fat tissue and muscle, associated with the appropriate imaging findings. 4 In our case, EBUS-TBNA was able to provide enough material for diagnosis, avoiding the need of a surgical intervention.…”
mentioning
confidence: 48%
See 2 more Smart Citations
“…Certainty diagnosis of mediastinal hamartoma is based on recognition of the characteristic fibromyxoid stroma or chondroid material with variable amounts of ciliated and nonciliated epithelium, fat tissue and muscle, associated with the appropriate imaging findings. 4 In our case, EBUS-TBNA was able to provide enough material for diagnosis, avoiding the need of a surgical intervention.…”
mentioning
confidence: 48%
“… 1 , 3 Mediastinal hamartomas are generally large and show a broad radiological differential diagnosis, which include malignancies, so histopathological examination should be performed 2 and needle aspiration can be appropriate in determining the diagnosis. 1 , 2 , 3 , 4 , 5 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Third, our research was a retrospective study and could cause selection bias, all our PH lesion were located in the peripheral lung, since it is rarely located in a hilar lesion or an endobronchial lesion. As for these special PH, it is reported in case report that endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) could be used to make diagnose (29,30) , but no studies have been reported in this regard. Last, the collection was not big enough to be convincing so further work needs to be done on providing a more extensive statistical database.…”
Section: Discussionmentioning
confidence: 99%
“…Diseases of the ear, nose, ear (ENT) itself has many kinds with a variety of symptoms caused. Many ENT diseases are caused by bacterial and viral infections that attack certain parts of the organ [8].…”
Section: Introductionmentioning
confidence: 99%